RETRACTED: Method of pruning apple tree crown size and increase in photosynthesis productivity - Yunusov Rustam; To`rayeva Nargiza (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001